FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI DALAM MELAKSANAKAN PEREMAJAAN KELAPA SAWIT DI KECAMATAN SUNGAI BAHAR KABUPATEN MUARO JAMBI - Yuli Ambarwati, Nadia; Napitupulu, Dompak; Yanita, Mirawati (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
This study aims to 1) study the description of the condition of oil palm rejuvenation using the simultaneous fall and underplanting technique in Sungai Bahar District, and 2) To analyze the factors that influence the decisions of oil palm farmers in replanting. This research was conducted in Suka Makmur and Mekarsari Makmur villages with a total of 30 farmers who did rejuvenation, 30 farmers who did underplanting rejuvenation and 30 farmers who did not replant. Data were analyzed using multinomial regression analysis. The results showed that at the research location two rejuvenation techniques were carried out, namely the simultaneous collapse technique which was funded by BPDPKS and the underplanting technique which was carried out independently by farmers. The simultaneous fall technique is carried out by uprooting all old plants which will be rejuvenated and then replaced with young plants. The underplanting technique is carried out by inserting young plants between old plants and then injecting them with the old plants as a method of gradual felling. The results of the analysis showed that the tendency of farmers to rejuvenate with the simultaneous collapse and underplanting technique was significantly influenced by the age of the farmers, the area of oil palm and the farmers' income at the 95% degree of confidence. The tendency of farmers to choose simultaneous rejuvenation is influenced by age which is 0,541 times smaller, the area of oil palm land is 11,428 times larger and the workforce in the family is 8,757 times greater than that of not doing replanting. The tendency of farmers to choose underplanting rejuvenation is influenced by the age of 0,279 times smaller, the area of oil palm land is 7,851 times larger and the workforce in the family is 2,940 times greater than that of not replanting.